Perencanaan Kurikulum Pendidikan pada Program Pembiasaan Pagi Pra-KBM di Sekolah Dasar Berbasis Islam ( Study Kasus di SD PLUS Darul Ulum Jombang) - Indah Nur Lathifiyah (INDO PUBLISHING, 2026)
This study aims to describe the curriculum planning of the Islamic-based pre-learning morning habituation program (Pra-KBM) at SD Plus Darul Ulum Jombang and to analyze its implementation in strengthening students' character within the framework of the Merdeka Curriculum. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, participant observation, and documentation involving the curriculum coordinator, habituation program coordinator, and teachers. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, consisting of data collection, data condensation, data display, and conclusion drawing. The findings reveal that the curriculum planning for the morning habituation program is systematically designed, integrated with the Merdeka Curriculum, and oriented toward developing students' character, spirituality, literacy culture, environmental awareness, and talents. The program includes flag ceremonies, literacy activities, Duha prayer, Qur'an memorization review (murojaah), istighotsah, collective shalawat, environmental planting activities, and the